Back pain in pregnancy - Mustafa, Kamarul Bahyah (Malaysia Association Of Maternal and Neonatal Health (MAMANEH), 2013)
Back pain or discomfort is common during pregnancy. It may be experienced during any point of pregnancy; even as early as the onset of pregnancy. However, the condition occurs most commonly later in the pregnancy as the weight of the baby increases. Berg and colleagues noted that about half of the 862 antenatal women developed some degree of low back pain. Seventy-nine women had severe enough low back pain stopping them to continue working and requiring referral to orthopaedic surgeon. Thus this condition should not be taken lightly- due to how common it is, and the fact that it can become severe.Women who are most at risk for back pain are those who are overweight or had back pain prior to pregnancy